The Flouting of Conversational Maxims in Make-Up Advertisements Found in People StyleWatch Magazine - Fifi Rania Maulida (Universitas Gadjah Mada, 2015)
This research aims to identify the types of conversational maxim that are flouted in the headlines and taglines of make-up advertisements found in three issues of People StyleWatch magazines published in August, September and October 2015, to study the implied meaning, and identify actions that a woman should take to be considered an ideal woman suggested by make-up advertisements. The result of the research shows that there are 25 headlines and taglines which flout the conversational maxims, namely maxims of quantity, maxims of quality, maxims of relation, andthe combination of the maxims. The result also shows that there are seven actions that a woman should take to be considered an ideal woman represented in each headline and taglines, namely wear make-up, wear make-up all day and everywhere, become beautiful in a fast and easy way, wear bold make-up, wear make-up to make the face healthier, wear make-up like models on the runway, and wear make-up everyday.